On structure of branched continued fractions - Antonova, T.M. (Karpats'kì matematinì publìkacìï, 2024)
The paper provides a survey of various multidimensional generalizations of continued fractions that arose when solving the problem of approximating functions of one or several variables, including some hypergeometric functions. It is shown that all these generalizations can be considered as separate cases of the general concept of a branched continued fraction, the definition of which is given in the work. У статті наведено огляд різних багатовимірних узагальнень неперервних дробів, які виникли при розв'язуванні задачі наближення функцій однієї чи багатьох змінних, включно з деякими гіпергеометричними функціями. Показано, що всі ці узагальнення можна розглядати як окремі випадки загального поняття гіллястого ланцюгового дробу, означення якого наведено у роботі.